Clinical Variability in Spinal Muscular Atrophy Type III. Issue 6 (2nd October 2020) - Coratti, Giorgia; Messina, Sonia; Lucibello, Simona; Pera, Maria Carmela; Montes, Jacqueline; Pasternak, Amy; Bovis, Francesca; Exposito Escudero, Jessica; Mazzone, Elena Stacy; Mayhew, Anna; Glanzman, Allan M.; Young, Sally Dunaway; et al.
Abstract : Objective: We report natural history data in a large cohort of 199 patients with spinal muscular atrophy (SMA) type III assessed using the Hammersmith Functional Motor Scale Expanded (HFMSE). The aim of the study was to establish the annual rate and possible patterns of progression according to a number of variables, such as age of onset, age at assessment, SMN2 copy number, and functional status. Methods: HFMSE longitudinal changes were assessed using piecewise linear mixed‐effects models. The dependency in the data due to repeated measures was accounted for by a random intercept per individual and an unstructured covariance R matrix was used as correlation structure. An additional descriptive analysis was performed for 123 patients, for a total of 375 12‐month assessments. Results: A break point at age 7 years was set for the whole cohort and for SMA IIIA and IIIB. Age, SMA type, and ambulatory status were significantly associated with changes in mean HFMSE score, whereas gender and SMN2 copy number were not. The increase in response before the break point of age 7 years is significant only for SMA IIIA (β = 1.79, p < 0.0001). After the break point, the change in the rate of HFMSE score significantly decrease for both SMA IIIA (β = −1.15, p < 0.0001) and IIIB (β = −0.69, p = 0.002). Interpretation: Our findings contribute to the understanding of the natural history of SMA type III and will be helpful in the interpretation of the real‐world data of patients treated with commercially available drugs. ANN NEUROL 2020;88:1109–1117